Screening for Language Difficulties in Disadvantaged Populations on Entry to Early Years Education: Challenges and Opportunities - Dockrell, Julie E.; Forrest, Claire L.; Law, James; Mathers, Sandra; Charlton, Jenna (Frontiers in Pediatrics, 2022)
Children aged 3–4 years (n = 876) were recruited from deprived areas in England, and a significant minority of the sample were second language learners. Oral language ability was assessed using child administered standardized measures, and parents reported on children’s language. We adapted the Language Use Inventory [LUI; (1)] to capture carer’s reports of the children’s structural language in the language of instruction and their home language (where appropriate). The final measure included six subscales from the original: use of simple words, requests for help, gaining attention, talking about activities/actions, interactions with others, and building sentences. Children’s language abilities and non-verbal abilities were below norms on all standardized tests administered except non-word repetition. Factor analysis indicated that all the six scales of the adapted parent completed measure loaded on one language factor. The revised total scale score correlated significantly (p < 0.0005) with child assessed language measures, specifically expressive vocabulary and grammar. Different patterns across gender, language status and parental education were examined. Sensitivity and specificity of the scale to identify children with the greatest delays were evaluated. These preliminary data indicated that parent-reported information on children’s language skills at 3 years of age has the potential to provide a reliable indicator to inform pedagogy and practice at the start of nursery school. Study limitations are examined and avenues for future development explored.